HUBUNGAN DUKUNGAN SUAMI TERHADAP KEHAMILAN DENGAN HIPEREMESIS GRAVIDARUM DI KLINIK PRATAMA RIDHO DESA BANDAR KHALIFAH TAHUN 2022 - Dian Zuiatna (Universitas Prima Indonesia, 2022)
A planned pregnancy will give a feeling of happiness to pregnant women, especially to the physical condition of pregnant women, namely changes in the body of pregnant women, an increase in pregnancy hormones such as HCG, estrogen and progesterone. This inability can cause changes in body function, especially the gastrointestinal system which ultimately results in nausea and vomiting called Hyperemesis Gravidarum. The purpose of this study was to determine the relationship between husband's support for pregnancy and hyperemesis gravidarum in first trimester pregnant women. This research is analytic in nature with a cross-sectional approach with a total population of 32 people using the total sampling technique. Data analysis was univariate analysis, bivariate analysis using the chi square test. The results of this study indicate a relationship between husband's support and pregnancy with hyperemesis gravidarum (0.021). It was concluded that husband's support for pregnancy is related to hyperemesis gravidarum in first trimester pregnant women at Ridho Pratama Clinic in 2022. It is hoped that there will be more good communication within the family, especially between husband and wife, so that during pregnancy the mother can get better husband support to improve welfare of the mother during pregnancy so as to reduce the number of morbidity experienced by the mother.